TREATMENT OF MINIMAL CHANGE DISEASE IN ADULTS: CURRENT PRACTICE AND FUTURE DIRECTIONS – A NARRATIVE LITERATURE REVIEW - Cezary Lubas; Joanna Kłosowska; Piotr Świerczek; Małgorzata Zach; Karolina Błądzińska; Maciej Błądziński; Kacper Szeląg; Antoni Kujawski; Paula Folta; Anna Opalińska (International Journal of Innovative Technologies in Social Science, 2025)
Research Objectives: This review aims to summarize the current therapeutic strategies for adults with MCD and to discuss future treatment directions in light of emerging immunological and molecular findings. Methods: Literature was searched using PubMed and Google Scholar, with a focus on studies from the past five years. Keywords used in the search included: „minimal change disease”, „nephrotic syndrome”, „glucocorticoids”, „rituximab”, „TRPC6”, and „adults”. Key Findings: Minimal change disease (MCD) is the most common cause of nephrotic syndrome in children and a significant contributor in adults. Although its clinical course in adults is often mild and steroid-responsive, many patients experience relapses, steroid resistance, or develop adverse effects related to prolonged glucocorticoid use. Glucocorticoids remain the first-line therapy for MCD, achieving remission in approximately 90% of adults, but relapses affect more than half of these patients. Alternative immunosuppressive therapies have shown comparable efficacy in inducing remission and may lower the relapse rate. Rituximab has shown significant therapeutic efficacy in steroid-dependent and frequently relapsing cases. Several new pharmacological agents - including TRPC6 inhibitors and ManNAc - are under investigation. Immunomodulatory therapies targeting B and T cells also show promise and are being explored in early-phase studies. Conclusions: MCD presents ongoing therapeutic challenges due to steroid-related toxicity, and heterogeneous treatment responses. A deeper understanding of the disease’s immunopathogenesis is opening new avenues for targeted and safer therapies. Further studies are needed to optimize treatment protocols and improve long-term prognosis and quality of life.